Moderator effect of COVID-19 fear on “mediating role of boredom proneness in relationship between internet addiction and DASS-21” - Halim Guner (Educational Process: International Journal, 2021)
Background/purpose – COVID-19 emerged at a time when many different psychological factors can negatively affect the human psychology, and thereby making life even more difficult over and above the physical health impact. As known, with the development of modern-day technology, Internet usage has become a part of everyday life. However, this situation often brings about the problem of Internet addiction. A positive relationship is known to exist between Internet addiction and psychological problems. This study aims to examine the moderator effect of COVID-19 fear on the “mediating role of boredom proneness in relationship between internet addiction and DASS-21.”